1986
DOI: 10.1007/bf00652244
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in plasma levels of 3,4-dihydroxyphenylethyleneglycol in major depression

Abstract: Plasma levels of free and sulfoconjugated 3,4-dihydroxyphenylethyleneglycol (DOPEG), the main deaminated metabolite of norepinephrine, were measured in a group of 45 hospitalized patients presenting a major depression and a group of 45 healthy subjects, matched for sex and age. Compared to healthy subjects, depressed patients had significantly lower plasma levels of free and sulfoconjugated DOPEG. The ratio of free over conjugated DOPEG was not statistically different in the two groups. The reduction of plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…In respect of the influence of the sex, our results are in agreement with those of Scatton et al [ 1986], while Loo et al [1983] found that in healthy people only free and total plasma DOPEG were higher in women than in men. As for MOPEG, our results are in agreement with those of Jimerson et al [1981a] and Halbreich et al [1987], In the present experiments, age did not seem to influence the plasma concentration of DOPEG in de pressive patients, as Loo et al [1983] found, while Scatton et al [ 1986] described a positive correlation between free DOPEG and age.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In respect of the influence of the sex, our results are in agreement with those of Scatton et al [ 1986], while Loo et al [1983] found that in healthy people only free and total plasma DOPEG were higher in women than in men. As for MOPEG, our results are in agreement with those of Jimerson et al [1981a] and Halbreich et al [1987], In the present experiments, age did not seem to influence the plasma concentration of DOPEG in de pressive patients, as Loo et al [1983] found, while Scatton et al [ 1986] described a positive correlation between free DOPEG and age.…”
Section: Discussionsupporting
confidence: 82%
“…As in the previous studies on DOPEG using a differ ent method of measurement, a significant decrease in the plasma levels was noted in depressed patients compared with the control subjects whatever the type or clinical form of the depression [Loo et al, 1983[Loo et al, , 1985Scatton et al, 1986].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Another point which deserves some comment is the fact that the concentrations of plasma sulfate-conjugated, but not free DOPEG (P>0.1) in the volunteers participating in this study are significantly lower (P < 0.001) than normal levels previously reported (Scatton et al 1986). It is thus possible that non-specific factors such as diet or physical effort can influence plasma sulfate-conjugated DOPEG levels.…”
Section: Discussionmentioning
confidence: 52%
“…We have recently shown that plasma free and conjugated DOPEG levels are significantly lower in depressed patients compared to normal volunteers (Scatton et al 1986). These subnormal levels of the noradrenaline metabohte would be consistent with the monoamine hypothesis of affective disorders which postulates that some forms of depression are associated with a deficiency of cerebral noradrenergic transmission (Schildkraut 1965;Maas 1975;Garver and Davis 1979).…”
mentioning
confidence: 99%